Pengaruh Faktor Internal dan Eksternal Terhadap Pelaksanaan Layanan Konseling Individual - Nurhadi, Siti; Suharso, Suharso (Universitas Negeri Semarang, 2016)
This research was based on preliminary datas of the interview against the teacher of Junior High School Tegal which shows that the implementation of the individualcounseling services has not to be implemented optimallyyet. The purpose of this research is to predict whether or not there are: (1) influence of internal factors against implementation of individual counseling service, (2)influence of external factors against implementation of individual counseling service, (3) the influence of internal and external factors against implementation of individual counseling services. The population of this research is the entire guidance and counseling teacher of SMP/MTs in Tegal. The methode of data collection using the technique of test and non-test. Data analysis technique using simple linier regression analysis and multiple regression. The result of the analysis indicate a significant and positive influence, there is strong internal factors against implementation of counseling services, external factors against implementation of counseling services, and internal and external factors together against the implementation of individual counselling service